NECESSITY AND USEFULNESS OF VEDIC THINKING IN THE CURRENT GLOBAL CONFLICT - Shekhawat, Ishvar Singh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the present world, humans have bound themselves, the monstrous forms of which are appearing before us. Man considers himself a part of a specific country and considers other countries of the world as separate from himself. Due to this, different countries are suffering mutual discrimination and causing harm to each other. Vedic thinking, which carries with it the special feeling of establishing the entire world as one home with the spirit of ’Vishvam Bhavatayekanidam’, is the only solution available to everyone which can help everyone walk on the path of peace and achieve mutual world brotherhood. Always paves the way for establishing the feeling. Due to its deep contemplation, it shows the way to move forward on the path of continuous development for the past, present and future. It inspires us to move forward together by showing the right path for mental, physical and spiritual development. It establishes an ideal life before everyone by abandoning the spirit of ’Ekla Chalo Re’ and reinforcing the spirit of ’Sangachchadhvam Samvaddhvam’.